Dictionnaire des imprimeurs, libraires et éditeurs des XVe et XVIe siècles dans les limites géographiques de la Belgique actuelle - Rouzet, Anne, (European History and Culture - Book Archive pre-2000., 1975)
Full biographies of some 800 Belgian printers and publishers of the 15th and 16th century, with a complete survey of the existing literature on each.